AB0277 Comparison between Intima-Media Thickness and Coronary Artery Tomography in Subclinical Atherosclerosis Detection in Rheumatoid Arthritis. (15th July 2016) - Riancho-Zarrabeitia, L.; Corrales, A.; Parra, J.A.; Santos-Gόmez, M.; Portilla, V.; Dessein, P.; Blanco, R.; González-Gay, M.A.
Abstract : Background: Intima media thickness (IMT) and coronary artery calcification (CAC) quantification using multidetector computed tomography (MDCT) scanner are useful in detecting subclinical atherosclerosis and are good surrogate markers of cardiovascular morbidity and mortality in general population and in rheumatoid arthritis (RA) A good correlation between these methods has been reported in RA, being CAC a slightly more sensitive technique (1) Objectives: Our aim is to determine the value of IMT that better predicts the presence of coronary atherosclerosis, using CAC as reference and assuming CAC value of 100 as the cut-off point indicating high cardiovascular risk. Methods: We evaluated 127 RA patients without previous cardiovascular events. Carotid ultrasonography was performed by a MyLab 70 scanner (Esaote; Genoa, Italy), equipped with 7–12 MHz linear transducer and the automated software guided technique radiofrequency – Quality Intima Media Thickness in real - time ( QIMT, Esaote, Maastricht, Holland ). According to data from non-rheumatic patients and also from RA patients, an IMT≥0.90 mm is a good predictor of high cardiovascular risk. To determine CAC score, a CT Imaging of coronary arteries using a 32-slice MDCT scanner (Lightspeed, Pro 32, GE Healthcare, USA) was performed. Results: Patients with IMT below 0.90 mm had CAC values of 88±210 whereas patients with IMT≥0.90 mm had mean CAC values of 190± 272 (p=0.066). We found a positive correlation between IMT and CAC (correlation coefficient 0, 303; p=0.001). The IMT cut-off value ≥0.90 mm had a sensitivity of 32% for detecting CAC ≥100. ROC curve analysis showed and area under the curve of 0.664. The IMT cut-off value of 0.80 mm had a sensitivity of 40% and a specificity of 71.3%. Lowering the IMT cut-off point to 0.70, we reached a sensitivity of 76% and a specificity of 51.5% for CAC ≥100 detection. The positive predictive value for the IMT cut-off point of 0.70 mm was 76% in our population, being the negative predictive value 49.5% Conclusions: IMT values ≥0.70 mm predict coronary artery calcification score above 100 with a sensitivity of 76%. According to that, the IMT value considered as predictor of high cardiovascular risk would be 0.70 mm instead of 0.90 mm. References: Corrales A et al. "Cardiovascular risk stratification in rheumatic diseases: carotid ultrasound is more sensitive than coronary artery calcification score to detect subclinical atherosclerosis in patients with rheumatoid arthritis" Ann Rheum Dis. 2013, 72 1764–1770. Disclosure of Interest: None declared